Bioactive zwitterionic polymer brushes grafted from silicon wafers via SI-ATRP for enhancement of antifouling properties and endothelial cell selectivity. Issue 18 (12th December 2017) - Wei, Yu; Zhang, Jingxun; Feng, Xiantao; Liu, Dongyin
Abstract: Zwitterionic copolymers keep good resistance to platelet adhesion and nonspecific protein adsorption. In this study, A block copolymer brushes consisting of carboxybetaine methacrylate (CBMA) and glycidyl methacrylate (GMA) were grafted from silicon wafers via surface-initiated atom transfer radical polymerization, and then the Arg-Glu-Asp-Val (REDV) peptide was attached to the polymer brush via an reactive epoxy group of the P(GMA) unit to improve endothelial cells (ECs) selectivity. These modified surfaces were evaluated with scanning electron microscopy, atomic force microscopy, attenuated total reflectance-Fourier transform infrared spectra, X-ray photoelectron spectroscopy, and static water contact angle measurement. The results showed that REDV-modified zwitterionic brushes were successfully constructed on silicon wafers. The biocompatibility of the membrane was determined by plasma recalcification time assay and platelet adhesion test. The results showed that the modified substrate exhibited good blood compatibility. Moreover, the proliferation of ECs and smooth muscle cells onto the REDV-modified copolymer brushes were examined to demonstrate the synergistic effect of CBMA with antifouling property and REDV peptide with ECs selectivity. All assays showed that the silicon wafers displayed excellent EC selectivity after modification. In summary, REDV-modified zwitterionic brushes had great potential for cardiovascular stent implantation.